Helical conformation of the AD1 peptide in the AML1-ETO–E-protein complex. Issue 3 (2009) - Porumb Porumb, Horea Horea
Abstract : The AML1-ETO fusion protein is responsible for 15% of the acute myeloid leukaemias due to its interference with transcription activation by E-proteins. The eTAFH region of the AML1-ETO competes for the AD1 domain of E-protein, thereby preventing wild-type transcription activation. The structural details concerning the eTAFH–bound AD1 domain are not known. We have previously shown that the eTAFH–AD1 interaction is strong ( K d =28 nM, H. Porumb, Spectroscopy 22 (2008), 251–260). The secondary structure prediction algorithms are undecided as to the conformation of bound AD1 peptide. Here we demonstrate by circular dichroism that the bound AD1 peptide is fully helical. This will facilitate modeling of the interaction and launches a challenge as to using synthetic peptides to out compete the eTAFH–E-protein interaction.